2014
DOI: 10.1063/1.4896059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of q-profile structure on turbulence spreading: A fluctuation intensity transport analysis

Abstract: This paper studies effects of q-profile structure on turbulence spreading. It reports results of numerical experiments using global gyrokinetic simulations. We examine propagation of turbulence, triggered by an identical linear instability in a source region, into an adjacent, linearly stable region with variable q-profile. The numerical experiments are designed so as to separate the physics of turbulence spreading from that of linear stability. The strength of turbulence spreading is measured by the penetrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…This increase in the characteristic interaction time has a stronger impact on spreading than the increase of the mode correlation length. Consequently, the overall spreading efficiency drops for low magnetic shear [66].…”
Section: Turbulence Front Propagation In the Linearly Unstable Zonementioning
confidence: 99%
“…This increase in the characteristic interaction time has a stronger impact on spreading than the increase of the mode correlation length. Consequently, the overall spreading efficiency drops for low magnetic shear [66].…”
Section: Turbulence Front Propagation In the Linearly Unstable Zonementioning
confidence: 99%
“…The emergence of turbulence spreading is considered to be one of the fundamental processes in the non-local transport [44]. Theoretical works demonstrated that spreading length of the turbulence is maximized around intermediate magnetic shear (S. Yi) [45] and the zonal flow prevents turbulence spreading in the weak shear case (J. Li). The ballistic propagation of the turbulence front can be induced through an avalanche process related to the self-organized criticality (SOC) models [46,47].…”
Section: Non-local Transport and Turbulence Spreading And Couplingmentioning
confidence: 99%
“…The mechanism most frequently involved for this is socalled turbulence spreading. [1][2][3][4][5] Turbulence spreading provides a natural way to contaminate stable domains, 6 as in the H ! L transition phenomena.…”
mentioning
confidence: 99%